Republic of Poland : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2012 Article IV Consultation discusses that the economy of Poland fared well throughout the crisis. The growth was robust and well balanced in 2011. The banking sector remained profitable and well capitalized. Declining provisioning boosted profitability and the average capital adequacy ratio remained high at about 13 percent. Executive Directors have commended the authorities for sound macroeconomic management, which has underpinned the good performance of the Polish economy in a challenging environment. Directors have broadly supported the ongoing fiscal adjustment, which is necessary to rebuild fiscal buffers.